Beyond Generalized Treatment: The Future is Personalized Medicine - Lakshay Virmani; Simran Kumari (Emerging Trends in Personalized Medicines, 2025)
Personalized medicine, which is also called as precision medicine, is reestablishing the view of new healthcare by replacing the traditional "one-size-fits-all" approach with individual therapies made according to a patients unique genomic organization, environment, and lifestyle. This article talks about the scientific foundation, important applications, ethical challenges, and the significant potential of personalized medicine in enhancing the clinical outcomes. From oncogenic and genetic disorders to chronic diseases, the addition of genomics, data analytics, and artificial intelligence is enabling great precision in diagnosis, prevention, and treatment. The paper also examines India’s growing role in the worldwide personalized medicine picture, underrated opportunities and barriers. As the field grows, personalized medicine has a vision which not only focusses on improved efficacy but also shows a sudden shift in patient-oriented care. Personalized medicine for cancer is at the forefront of the new bioeconomy and visions for the future of healthcare. It also promises the treatments designed to individuals, genomes and those of their cancers, as well as more precise diagnosis, prognosis and prevention. Widely celebrated as revolutionary and transformational, the risks and ethical issues of personalized medicine are confronted every day by patients, clinicians and researchers, but are consistently underplayed in the main stream media.
Keywords: Genomics; Personalized medicine; artificial intelligence; ethical challenges; patient- oriented care